Credit risk and disaster risk - François Gourio (Federal Reserve Bank of Chicago, 2012)
Credit spreads are large, volatile and countercyclical, and recent empirical work suggests that risk premia, not expected credit losses, are responsible for these features. Building on the idea that corporate debt, while safe in ordinary recessions, is exposed to economic depressions, this paper embeds a trade-off theory of capital structure into a real business cycle model with a small, exogenously time-varying risk of economic disaster. The model replicates the level, volatility and cyclicality of credit spreads, and variation in the corporate bond risk premium amplifies macroeconomic fluctuations in investment, employment and GDP.
Keywords: E32; E44; G12; 330; financial frictions; financial accelerator; systematic risk; asset pricing; credit spread puzzle; time-varying risk premium; disasters; rare events; jumps